2000
DOI: 10.1074/jbc.m910211199
|View full text |Cite
|
Sign up to set email alerts
|

Transducin-like Enhancer of Split Proteins, the Human Homologs of Drosophila Groucho, Interact with Hepatic Nuclear Factor 3β

Abstract: Members of the hepatic nuclear factor 3 (HNF3) family, including HNF3␣, HNF3␤, and HNF3␥, play important roles in embryonic development, the establishment of tissue-specific gene expression, and the regulation of gene expression in differentiated tissues. We found, using the glutathione S-transferase pull-down method, that the transducin-like Enhancer of split (TLE) proteins, which are the human homologs of Drosophila Groucho, directly associate with HNF3␤. Conserved region II of HNF3␤ (amino acids 361-388) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…This PCR fragment was then digested by BamHI and XbaI and subcloned into pSG424 plasmid (39). Construction of GAL4-TLE1 and (GAL4)5E1BLuc reporters (40,41) and assays for ␤-galactosidase and luciferase activity (42) have been described previously. A549 cells were maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…This PCR fragment was then digested by BamHI and XbaI and subcloned into pSG424 plasmid (39). Construction of GAL4-TLE1 and (GAL4)5E1BLuc reporters (40,41) and assays for ␤-galactosidase and luciferase activity (42) have been described previously. A549 cells were maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the other subgroup, e.g., Grg5 in mice and AES in humans, contain the amino-terminal region of gro, including the Q-rich domain, but lack most of the variable region and the entire WD-40 repeat region. Mammalian gro homologues in the first group bind to transcription factors that target gene repression (Aronson et al, 1997;Roose et al, 1998;Eberhard et al, 2000;Tetsuka et al, 2000;Wang et al, 2000;Brantjes et al, 2001), whereas the short form of gro, such as XGrg5 in Xenopus, has been shown to enhance transcriptional activity (Roose et al, 1998;Brantjes et al, 2001). It has been speculated that Grg5 may act as a dominant negative molecule within a transcription complex.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that the transducin-like enhancer of split (TLE, a mammalian Groucho homolog) protein directly interacts with region II sequences of the HNF-3␤ activation domain and that HNF-3␤ interactions with TLE protein diminish its transcriptional activation in cotransfection assays. 43 Given the fact that increased hepatic HNF-3␤ levels caused decreases in many of its regulatory partners required for synergistic transcriptional activation of hepatocyte genes, HNF-3␤ interaction with the Groucho ESP1 homolog provides a plausible explanation for the observed repression of HNF-3␤ target gene expression. In transient-transfection assays HNF-3␤ has been found to regulate the promoter activity of Glut-2 gene and synergize with HNF-1␣ to activate Glut-2 promoter expression.…”
Section: Tan Et Al Hepatology January 2002mentioning
confidence: 99%